Web Scraper Dan Graphql API Untuk Data Perguruan Tinggi Di Indonesia Berdasarkan Website Kementerian Ristekdikti (Studi Kasus: Website Kementerian Ristekdikti) - Lingga Tiara; Hadi Syaputra; Widya Cholil; A.Haidar Mirza (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2021)
The urge to obtain and transmit information is one of the reasons for current technological developments, such as the need for students to access higher education reporting forums or Forlap Dikti. Forlap Dikti is a website page developed by the Ministry of Research, Technology and Higher Education that contains data on student academic activities based on reporting data from universities in Indonesia. Therefore we need a support application to be able to facilitate and expedite the need for access to information on the Forlap Dikti website page using the android application. This study aims to: (1) Help collect student data as material for presenting the required information, (2) Design an application as a medium for finding information on student data at Bina Darma University, (3) With an efficient web scraping function it also helps in data analysis. This application uses puppeteer for scraping data from websites, App Inventor and GraphQL API to display student data.